Copper-mediated aerobic oxidative synthesis of benzimidazo fused quinazolines via a multicomponent approach1. Issue 104 (11th November 2015) - Rai, Byanju; Kumar, Promod; Kumar, Atul
<x xml:space="preserve">Abstract</x> First copper mediated aerobic oxidative multi-component synthesis of benzimidazo[1, 2-c]quinazolines has been developed from 2-(2-halophenyl)benzoimidazoles, aldehydes and sodium azide as nitrogen source.